Investigating the retarding effect of CAC in alkali-activated cements - Stefanini, Laura; Walkley, Brant; Provis, John L. (Frontiers in Materials, 2023)
This paper discusses the design of hybrid alkali-activated binders at ambient temperature, specifically the development of mixes based on ground granulated blast-furnace slag (GGBFS) with calcium aluminate cement (CAC) as an additive, aiming to obtain high early strength binders with optimised Al incorporation, increased crosslinking and degree of polymerisation. The effects of 10 wt% CAC replacement of GGBFS, activated with sodium silicate with varying modulus (SiO2/Na2O molar ratio) or with sodium hydroxide, on fresh and hardened properties are investigated. The inclusion of CAC in GGBFS mixtures activated using sodium silicate results in an unexpected retardation of the polycondensation reactions required to form the main calcium aluminosilicate hydrate gel phase. This is due to incomplete dissolution of the GGBFS precursor, inhibited by the rapid formation of additional reaction products (especially cubic aluminate hydrates, C3AH6) resulting in lowered reaction kinetics, and thus delayed setting and hardening times. For sodium silicate activators, this retarding effect appears to be only slightly dependent on the activator solution modulus. When activating with 4 M NaOH, the retarding effect is reduced, along with the incorporation of CAC in the C-A-S-H gel, increasing the amount of reactive aluminium present in the binder to form a more compact gel product. Increasing the molarity of NaOH solutions results in a similar delay in reaction kinetics. The results suggest the existence of only a limited pH range in which the addition of CAC can promote the formation of a binding gel with enhanced mechanical properties, whilst other factors including the effect of sodium silicate inclusion in CAC systems are still unclear. The typical hydration products of CAC were not detected in this study.